Median nerve impairment in leprosy: how does it differ from the classic carpal tunnel syndrome? - Alves, Pedro Henrique Sirotheau Corrêa; Cirino, Fernanda de Oliveira; Garcia, Leonardo Peixoto; Fernandes, João Paulo Moreira; Luppi, Andrea De Martino; Antunes, Douglas Eulálio; Pereira, Raquel Campos; Junior, Wilson Marques; Goulart, Isabela Maria Bernardes; Santos, Diogo Fernandes dos (Arquivos de Neuro-Psiquiatria, 2024)
Background Carpal tunnel syndrome (CTS) has already been described as a possible form of neural leprosy presentation. However, the median nerve can be involved in this neuropathy in proximal segments and, sometimes, with an asymmetric impairment of the digital branches.Objective To detail the pattern of median nerve impairment through nerve conduction study (NCS) and ultrasound evaluation.Methods This cross-sectional study comprises 15 primary neural leprosy (PNL) patients and 14 patients with CTS who underwent peripheral nerve ultrasonography and NCS evaluation.Results From the total, 92.8% of patients with CTS and 80% with PNL had bilateral impairment of the median nerve, with 27 nerves in each group. Considering the cross-sectional area (CSA) of the tunnel (Mt) segment, 63% of the nerves in the CTS and 74.1% in the PNL groups were found to be thickened, with an average CSA of 13.4 ± 4.4 and 12.4 ± 4.6, respectively (p = 0.18). The CSA of the proximal tunnel (Mpt) segment showed thickening in only 3.7% in the CTS group and 96.3% in the PNL (p < 0.0001), with an average of 6.6 ± 1.3 and 17.0 ± 6.7, respectively (p < 0.001). Finally, 88.9% of the nerves in the PNL group and only 7.4% in the CSA (p < 0.0001) showed a reduction in conduction velocity in the distal forearm, with an average of 41.0 ± 6.3 and 53.2 ± 5.2, respectively (p < 0.0001).Conclusion The presence of neural thickening and demyelinating impairment in the segments proximal to the carpal tunnel favors the diagnosis of leprosy.
Keywords: Leprosy; Peripheral Nerves; Ultrasonography; Mycobacterium leprae; Electromyography